Chilling Injury in Tropical Foliage Plants: III. Dieffenbachia - Jianjun Chen (EDIS)
A chilling temperature is any temperature that is cold enough to cause plant injury but not cold enough to freeze the plant. Chilling injury can occur to tropical foliage plants if greenhouses become too cold or if the plants are exposed to chilling temperatures outside of the greenhouse during packing and shipping. Dieffenbachia, commonly known as dumb cane, ranks among the top five most popular foliage plant genera produced and sold in the United States. This 4-page fact sheet describes the chilling temperatures of Dieffenbachia cultivars in order to assist growers to better manage greenhouse temperatures. Written by Jianjun Chen and published by the Environmental Horticulture Department, July 2016.